PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP PEMBELIAN PRODUK ERIGO - Laura Theodora Loviga; Mohamad Trio Febriyantoro (Gapenas Publisher, 2023)
The purpose of this study is to determine the influence of variable Brand Image, Price, and Product Quality on purchasing decisions on Erigo purchases. The data collection technique using a questionnaire was then tested through validity and reliability and the samples used in this study were 112 respondents using the analysis method used was multiple linear regression using SPSS 23 software. The result of this study is that the Brand Image variable and the Product Quality variable affect Erigo's Purchasing Decision, while the Price variable does not affect the Purchase Decision